Comprehensive analysis of carotenoids constituents in purple-coloured leaves and carotenoid-derived aroma differences after processing into green, black, and white tea. (1st January 2023) - Shi, Jiang; Wu, Wenliang; Zhang, Yongcheng; Baldermann, Susanne; Peng, Qunhua; Wang, Jiatong; Xu, Lili; Yang, Gaozhong; Fu, Jianyu; Lv, Haipeng; Lin, Zhi
Abstract: Carotenoids differentiate among tea cultivars and play role in contributing aroma flavor and colour appearance in tea products. In this study, 3 carotenes and 16 xanthophylls were accurately quantified of 0.79–1.56 × 10 3  μg g −1 in 15 tea cultivars possessing leaves of different colours. Lutein and β-carotene accounted for >80% of total carotenoids. Single carotenoid accumulation patterns and their correlations with chlorophylls and primary metabolites (amino acids, alkaloids, and saccharides) were elucidated. Tea processing (withering, 'kill-green, ' fermentation, and drying processes) decreased tea carotenoids by >65%, promoting volatile apocarotenoid production. In total, 25 crucial carotenoid-derived aroma compounds were detected in green, white, and black teas prepared from purple shoots. Additionally, α/β-ionone and their derivates, and dihydroactinidiolide accounted for >50% of total volatiles and therefore explained the fruity aroma in purple tea products. A comprehensive integrative analysis of sensory attributes and volatile and carotenoid precursor dynamics clearly revealed patterns of tea carotenoid accumulation and degradation contribution to tea aroma. Graphical abstract: Image 1 Highlights: Lipid-soluble pigments in green-, yellow-, and purple-leaf teas were compared. Carotenoid and chlorophyll correlations in purple-coloured leaves were unraveled. Strong connection among primary metabolites and lutein accumulation were confirmed. Carotenoid-derived aroma in tea products prepared from purple leaves were analysed.